RASIO KEUANGAN DAN PERTUMBUHAN ENTITAS TERHADAP NILAI PERUSAHAAN - Palupi, Tisa Indah; Tjahjono, Rudi Setiadi (E-Jurnal Akuntansi TSM, 2023)
The purpose of this study is to obtain empirical evidence that the independent variables return on assets, debt to asset ratio, firm size, company growth, dividend policy, independent commissioners, and board size have an influence on the dependent variable, namely firm value. In this study, the population used was manufacturing companies listed on the Indonesian stock exchange from 2019 to 2021 with the purposive sampling method used. The data obtained were 120 manufacturing company data. The test used in this study is multiple regression which helps to determine the influence between the dependent variable and the independent variable. The results of this study indicate that the variables return on assets, debt to asset ratio, company growth, independent commissioners, and board size have an effect on firm value. Meanwhile, the variable firm size and dividend policy have no effect on firm value.